Livelihood Study of the Second-Generation Households of Resettlement in Koto Panjang Hydropower Region, Riau Province - Tince Sofyani; Syafruddin Karimi; Melinda Noer; Suardi Tarumun (Universitas Andalas, 2018)
The construction of dams in many cases has led to forced displacement and resettlement of about 40-80 million people worldwide. Several studies have reported that Development Induced Displacement and Ressettlement (DIDR) cause negative impacts on living standards and livelihood outcomes of the resettled communities. Koto Panjang Dam has been in operation for 20 years. The impact of settlement movement due to the construction of a long Koto Panjang dam is also experienced by second generation resettlers. The objectives of this study were: a) to assess the profile access and control on household farming livelihood of second generation of resettlers, and b) to assess the level of household welfare of the second generation in Koto Panjang hydropower region, Riau Province. All second-generation households in Koto Mesjid and Pongkai Istiqamah were taken for samples (92 households). Profile access and control on households farming at the site of this study showed that men still dominated in access and control on farm management such as: land, working, credit, means of production, breeding, pest and disease control, education, training, and agricultural extension. Women were more dominant in processing and selling the yields. The poverty experienced by households in Koto Masjid village was largely due to limited land ownership, while that experienced by households in Pongkai Istiqomah village was due to the dependence of livelihoods on the rubber plantation, in addition to the limited field of other businesses in the village.